Kroatischer Nationalismus und Panslawismus in Argentinien und Chile während des Ersten Weltkriegs - Martínez-Flener, Milagros; Prutsch, Ursula (Anuario de Historia de América Latina, 2018)
The present article deals with the development of Southern Slav nationalism among former subjects of the Austro-Hungarian Monarchy in South America in the years before and during World War I. The article focuses on Chile and Argentina, but also takes the transnational characteristics of the nationalist Slav movement into consideration, which established strong transatlantic connections with the Yugoslav Committee in London and links with national committees in the United States. Chile became the center of the Southern Slav movement in Western South America. It provided the committee in London not only with considerable sums of money, but also with intensive propaganda activities which first sought to gain adherents among the emigrated Croatian and Dalmatian subjects of the Habsburg Empire. The diplomatic representatives of the Dual Monarchy found themselves confronted with a political situation, which they initially sub-estimated, but were not able to deal with later.
Keywords: South America; World War I; Nationalism; South Slavs; Austro-Hungarian Monarchy